2016
DOI: 10.2807/1560-7917.es.2016.21.44.30390
|View full text |Cite
|
Sign up to set email alerts
|

Summer music and arts festivals as hot spots for measles transmission: experience from England and Wales, June to October 2016

Abstract: We report 52 cases of measles linked to music and arts festivals in England and Wales, between mid-June and mid-October 2016. Nearly half were aged 15 to 19 years. Several individuals who acquired measles at one festival subsequently attended another festival while infectious, resulting in multiple interlinked outbreaks. Transmission within festivals resulted in a geographical spread of cases nationally as well as internationally, which presents particular challenges for measles control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…The use of triangulation also enabled us to determine that, despite good coverage overall, there was a high proportion of susceptible individuals among those born between 1998 and 2004 (who were aged between 15 and 22 years in 2019), even after adjusting for coverage under-ascertainment. This finding was consistent with disease incidence data, which showed that most cases and outbreaks in recent years occurred in this age group 24 . In England, where vaccine coverage is assessed using various methods, our synthesis of data from two different vaccine coverage sources led to insights into the vaccination status of the population.…”
Section: Discussionsupporting
confidence: 87%
“…The use of triangulation also enabled us to determine that, despite good coverage overall, there was a high proportion of susceptible individuals among those born between 1998 and 2004 (who were aged between 15 and 22 years in 2019), even after adjusting for coverage under-ascertainment. This finding was consistent with disease incidence data, which showed that most cases and outbreaks in recent years occurred in this age group 24 . In England, where vaccine coverage is assessed using various methods, our synthesis of data from two different vaccine coverage sources led to insights into the vaccination status of the population.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, at the time of writing (August 2016), there are already cases of measles in teenagers and young people linked to music festivals in the UK where this age group is predominant and mixing patterns are intense. 25 26 Moreover, children from this age group who go on to enter employment in educational or healthcare settings may mix with highly vulnerable infants too young to be vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-two were not vaccinated. Nine cases were not fully vaccinated, or their immunization status was unknown [83].…”
Section: Others Religious Meetingsmentioning
confidence: 99%